Lipid Composition and Physicochemical Parameters of Flaxseed Oil (Linum usitatissimum L.) from Bulgaria - Vanya Gandova; Olga Teneva; Zhana Petkova; Ivan Iliev; Albena Stoyanova (Applied Sciences, 2023)
Flaxseed oil is a prevalent food supplement. On one hand, vegetable oil is used in the food industry and pharmacy due to its health benefits; on the other hand, it has an application as a lubricant oil. The fatty acid composition of the investigated oil was determined as follows: the main fatty acids were α-linolenic (57.5%), oleic (17.5%), linoleic (12.5%), palmitic (6.0%), and stearic acid (4.3%). The content of unsaponifiable matter was 1.4%. The total sterol content was determined (0.5%), with identified β-sitosterol (79.7%) as a main component, followed by stigmasterol. The content of tocopherols was found to be 243 mg/kg. The compound γ-tocopherol predominated (68%) in the tocopherol fraction, followed by γ-tocotrienol (32%). Some physicochemical indicators were also determined—density, surface tension, and dynamic and kinematic viscosity—at the following temperatures: 20, 30, 40, 50, 60, 70, and 80 °C. The increase in temperature led to a decrease in all indexes and good linear dependence was observed. The determined physicochemical indicators provided information about the stability of flaxseed oil, which is very important considering its use in food and technical products.